Strategi Penguatan dan Dinamika Implementasi Rule of Law dalam Mewujudkan Transformasi Hukum Indonesia yang Berkeadilan - Shafira Ramadhani; Muhammad Akbar Junaidi; Zaenul Slam (Jurnal Pendidikan Kewarganegaraan dan Politik, 2026)
This study is designed to explore how the rule of law is implemented and strengthened in Indonesia. As a nation governed by the rule of law, Indonesia not only applies this principle to comply with formal regulations but also uses it as a means to achieve real justice for the people. To examine this, this study uses normative legal methods by examining existing legal concepts and history. The analysis shows that basic principles of the rule of law, such as human rights and equality before the law, play a crucial role in limiting the power of those in power and guiding legal change in Indonesia. However, in its implementation, Indonesia still faces challenges in the form of regulatory inconsistencies and a legal culture that has not fully adapted to changing times. Therefore, the legal system needs to be strengthened through several important steps, namely improving bureaucratic procedures, utilizing technology in the judicial process, and increasing the honesty of law enforcement officials. These strategic steps are key to realizing a more modern, transparent, and just legal transformation in Indonesia for all levels of society.